Analisis Keputusan Investasi Bagi Usaha Mikro, Kecil Dan Menengah (UMKM) - Suprapto, Heru (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2007)
Theoretically decision of invesment specially to UMKM influenced by environmental aspect business. From result of research indicate that only eksternal environment which forming model decision of invesment that is environmental direct eksternal and environment public eksternal. Internal environment of business in the reality is not become consideration in conducting invesment to UMKM, though internal capacities in managing business very required for the efficacy of an effort. Key Word : Lingkungan eksternal langsung, lingkungan eksternal umum, lingkungan internal bisnis.